Analisis Perbandingan Tingkat Kesehatan BPR Konvensional dan BPR Syariah Central di Kota Batam - Martius, Martius (Jurusan PIPS FKIP UMMY Solok, 2017)
Banking is one institution that an important role in the economic field of a country. Banking is anything about the bank, including institutions, business activities, and ways and processes in carrying out its business activities. The development of BPR businesses that continue to show positive performance is driven by three main factors: government policies that provide opportunities for BPR establishment, banking deregulation that enlarges the BPR space and the large needs of the community, especially in rural and urban areas, towards banking services. This research was conducted to know the analysis of the difference of health level in matters of Capital aspect, Asset, Management, Rentability, Liquidity and Capital between Conventional BPR and Syariah. Population in this research is all financial data of Conventional Rural Bank and BPR Syariah Kota Batam registered at Bank Indonesia. The sample in this research is the financial data of Conventional BPR and BPR Syariah in Batam for 2 years. Data analysis method used is CAMEL method. To measure the level of health of banking companies in general use Ratio Asset Quality and Earnings ,. Judging from the method of Quality Asset Ratio and Earning is generated a very good weight value so it can be concluded that the Conventional and Syariah Banks in 2014 and 2015 are in the healthy category.